2022
DOI: 10.1039/d2cp01019d
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of direct CO2 hydrogenation to methanol on Pd surfaces

Abstract: The reaction mechanism of direct CO2 hydrogenation to methanol is investigated in detail on Pd (111), (100) and (110) surfaces using density functional theory (DFT), supporting investigations into emergent Pd-based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 62 publications
2
14
1
Order By: Relevance
“…It should be pointed out that the paths of CH 2 O + OH → H 2 COOH and CH 2 O + O → H 2 COO were ignored in the previous DFT studies of methane oxidation ,, and first observed in our present work. In previous studies, H 2 COO and H 2 COOH have been reported during the hydrogenation of CO 2 to methanol . Such two steps can be observed due to the high activity of lattice oxygen and the smaller barriers of 0.20 and 0.57 eV compared with the dehydrogenation of CH 2 O to CHO with the barrier of 1.15 eV, which might provide alternative mechanisms at a molecular level to form the complete oxidation product CO 2 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It should be pointed out that the paths of CH 2 O + OH → H 2 COOH and CH 2 O + O → H 2 COO were ignored in the previous DFT studies of methane oxidation ,, and first observed in our present work. In previous studies, H 2 COO and H 2 COOH have been reported during the hydrogenation of CO 2 to methanol . Such two steps can be observed due to the high activity of lattice oxygen and the smaller barriers of 0.20 and 0.57 eV compared with the dehydrogenation of CH 2 O to CHO with the barrier of 1.15 eV, which might provide alternative mechanisms at a molecular level to form the complete oxidation product CO 2 .…”
Section: Resultsmentioning
confidence: 92%
“…To understand the details of the formation process of the complete oxidation product CO 2 over PdO (101), here the trajectory of every CH 4 molecule that participates in the reactions is analyzed and summarized in Scheme 1. As Scheme 45 Such two steps can be observed due to the high activity of lattice oxygen and the smaller barriers of 0.20 and 0.57 eV compared with the dehydrogenation of CH 2 O to CHO with the barrier of 1.15 eV, which might provide alternative mechanisms at a molecular level to form the complete oxidation product CO 2 . Our simulations show that 11 methane molecules dissociate and no CO 2 is formed on the Pd (111) surface with oxygen coverage of 3/9 ML, while 21 methane molecules dissociate and CO 2 is observed on the PdO (101) surface, indicating that PdO may be more active than Pd for methane oxidation.…”
Section: Methane Oxidation On the Pdo (101) Surfacementioning
confidence: 99%
“…CO 2 utilization has attracted much attention with the rapid development of sustainable hydrogen. 1–5 Among the various utilization options, CO 2 hydrogenation to methanol (CO 2 + 3H 2 ⇋ CH 3 OH + H 2 O, = −49.3 kJ mol −1 ; = +3.5 kJ mol −1 ) is a preferable candidate since methanol is an important chemical intermediate and liquid fuel. 1 A methanol economy was even proposed for CO 2 utilization by Prof. George Andrew Olah, 6 based on CO 2 hydrogenation to methanol.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 utilization has attracted much attention with the rapid development of sustainable hydrogen. [1][2][3][4][5] Among the various utilization options, CO 2 hydrogenation to methanol (CO 2 + 3H 2 ! CH 3 OH + H 2 O, DH 298K = À49.3 kJ mol À1 ; DH 298K = +3.5 kJ mol À1 ) is a preferable candidate since methanol is an important chemical intermediate and liquid fuel.…”
Section: Introductionmentioning
confidence: 99%
“…The different means of CO 2 chemical fixation, separation, and conversion to improve its storage are being currently developed. 27,[35][36][37][38][39][40][41][42][43] The synthesis of valuable reactants out of abundant CO 2 instead of its geological storage represents a perspective and seemingly quite successful direction of research in synthetic chemistry. The latter greatly benefits from the explosive development of novel fascinating catalysis schemes.…”
mentioning
confidence: 99%